Developing and Implementing Low-Cost Remote Laboratories for Undergraduate Biology and Neuroscience Courses - Hanzlick-Burton, Camden (J Undergrad Neurosci Educ, 2020)
The global pandemic caused by the novel coronavirus (SARS-COV-2) has forced many universities to abruptly change the delivery of courses from in-person to online. This change to remote learning requires creating new ways to deliver lectures, exams, and discussion groups through online meeting platforms. An often-overlooked challenge is performing lab courses that require access to specialized equipment and resources typically found in the undergraduate laboratory classrooms. Here we discuss some strategies for developing and implementing a full semester neuroscience laboratory course that allows students to fully participate in laboratory exercises at home or in their dorm rooms. Performing lab exercises remotely and independently was shown to significantly improve participant’s self-efficacy and confidence that they can learn complex neuroscience material, when compared to participants who passively watch experiments online. We review best practices to ensure that lessons can be successfully demonstrated by the instructor and carried out by all students. Finally, we discuss the need to provide a level playing field such that all students may succeed, regardless of their current technology resources at home.